Health Benefits, Therapeutic Applications, and Recent Advances of Cirsilineol in the Medicine: Potential Bioactive Natural Flavonoids of Genus Artemisia - Patel, Dinesh K. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Herbal medicine and its derived products have been used in the medicine and nutraceutical sectors for the treatment of human disorders and associated secondary complications. Plant-derived products play an important role in our daily life due to their medicinal properties and pharmacological activities. The attention of scientists to natural products has increased due to their significant biological activities. Flavonoids represent one of the most important phytocompounds present in the higher plants, common fruits, vegetables, herbs, wine, juices, and dried fruits. Flavonoids exert potent antioxidant activity by blocking and scavenging free radicals. Cirsilineol, also called 4',5-dihydroxy-3',6,7-trimethoxyflavone, is an active phytochemical of Artemisia vestita, Artemisia monosperma, Artemisia asiatica, and Agrostis gigantea. Medicinal importance and pharmacological activities of cirsilineol have been investigated in the present work with their analytical aspects in order to know the biological importance of cirsilineol in medicine. Literature data on cirsilineol were collected and analyzed in the present work to study its therapeutic potential against various human disorders and associated secondary complications. Scientific data were collected from Google, Google Scholar, PubMed, Science Direct, and Scopus and analyzed in the present work using the term herbal medicine, flavonoid and cirsilineol. Medicinal plants containing a significant amount of cirsilineol have biological applications in medicine due to their pharmacological activities. This present work signifies the biological importance of cirsilineol in medicine as it has antiproliferative, gastroprotective, anti-Helicobacter pylori, anti-diabetic and anti-oxidant activities. Further therapeutic effectiveness of cirsilineol against different types of cancers, including breast carcinoma and lung carcinoma, has been discussed in the present work. The biological importance of cirsilineol against allergic rhinitis, inflammation, coronavirus, immune system, renal cellular membrane and protein glycation has also been discussed in the present work. However, the importance of analytical methods for the isolation and identification of cirsilineol in medicine has also been analyzed. This work aimed to summarize the health-beneficial aspects of cirsilineol in medicine which will be beneficial to explore the further therapeutic effectiveness of cirsilineol for the treatment of various forms of human disorders.
Keywords: Spirometry